Case Report: PNPLA2 Gene Complex Heterozygous Mutation Leading to Neutral Lipid Storage Disease With Myopathy - Shi, Jiejing; Qu, Qianqian; Liu, Haiyan; Zhang, Yan; Cui, Wenhao; Chen, Ping; Lv, Haidong (Frontiers in Integrative Neuroscience, 2021)
[Abstract] : Objective To investigate the clinical features, skeletal muscle imaging, muscle pathology, blood smear and so on of neutral lipid storage disease with myopathy(NLSDM) caused by PNPLA2 gene mutation. Methods The clinical data, skeletal muscle imaging and pathological data, and genetic test results of a patient with NLSDM treated in our hospital were collected in detail, and the previous literature was reviewed and compared. Results The main symptoms were muscle weakness and muscular atrophy. Pathological findings of muscle biopsy showed fat deposition in muscle fibers with border cavitation. Fatty droplets are seen in the cytoplasm of neutrophils in peripheral blood. Magnetic resonance imaging of the muscles of both lower extremities showed that the thigh vastus intermediates, lateral muscles, biceps, and the muscle abdominal area of the middle leg were filled or replaced by fat. Genetic results suggested mutations in the PNPLA2 gene. Conclusion NLSDM is a rare muscle disease with abnormal lipid metabolism in clinical practice. Characteristic changes can be seen in skeletal muscle imaging and pathology. PNPLA2 gene mutation is the most important basis for the diagnosis of neutral lipid storage disease with myopathy.